2018
DOI: 10.5505/tjtes.2017.34514
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β-glucan on serum level of IL-12, hs-CRP and clinical outcomes in Multiple trauma patients: a prospective randomized study

Abstract: ß-glucan may increase serum levels of IL-12, shorten the duration of mechanical ventilation, and reduce organ failure in critically ill multiple-trauma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Similar results in feeding volume and energy intake were observed in the administration of this supplement for 21 days in critically ill patients 20 . However, studies on the efficacy of probiotics in ICU patients have reported contradictory results, from ineffectiveness and even side effects of probiotics to beneficial effects in improving enteral feeding tolerance, depending on the studied population, cause of hospitalization, product format, and study design 12,21–26 . Given that one of the main reasons for obtaining contradictory results on the efficacy of probiotics was the initial differences in the studied population, the present study was performed only on a population of critically ill patients with similar baseline characteristics, fixing this flaw of the previous studies.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Similar results in feeding volume and energy intake were observed in the administration of this supplement for 21 days in critically ill patients 20 . However, studies on the efficacy of probiotics in ICU patients have reported contradictory results, from ineffectiveness and even side effects of probiotics to beneficial effects in improving enteral feeding tolerance, depending on the studied population, cause of hospitalization, product format, and study design 12,21–26 . Given that one of the main reasons for obtaining contradictory results on the efficacy of probiotics was the initial differences in the studied population, the present study was performed only on a population of critically ill patients with similar baseline characteristics, fixing this flaw of the previous studies.…”
Section: Discussionsupporting
confidence: 53%
“…20 However, studies on the efficacy of probiotics in ICU patients have reported contradictory results, from ineffectiveness and even side effects of probiotics to beneficial effects in improving enteral feeding tolerance, depending on the studied population, cause of hospitalization, product format, and study design. 12,[21][22][23][24][25][26] Given that one of the main reasons for obtaining contradictory results on the efficacy of probiotics was the initial differences in the studied population, the present study was performed only on a population of critically ill patients with similar baseline characteristics, fixing this flaw of the previous studies. Unlike previous studies showing equivocal results from probiotic use that were due, in part, to differences in study population, our study groups were statistically comparable.…”
Section: Discussionmentioning
confidence: 99%
“…The full texts of the 33 remaining studies were examined to determine their eligibility, and 10 studies were excluded. Finally, 23 RCTs were selected for systematic review and meta-analysis (16)(17)(18)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). The detailed workflow is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Malik et al demonstrated that probiotic administration was associated with significantly lower ICU LOS [26]. Other studies found no significant difference between groups, regarding ICU or hospital LOS [19,21,22,24,27,[30][31][32][33].…”
Section: Effect On Length Of Staymentioning
confidence: 99%
“…The number of days of diarrhea was also investigated in two studies, one of which reported a significant decrease [25], while the other found a non-significant increase [28]. The number of liquid stools was also reported to be lower in the prebiotic group in one trial [21].…”
Section: Effect On Diarrheamentioning
confidence: 99%